Pancasila Education Teachers and the Merdeka Curriculum: A Deep Learning Approach to Character Development in Grade X Students at SMAN 4 Singaraja - Sawu, Antonius Nelson Tonda; Budiarta, I Wayan; Sukadi; Elita, Bernadeta Lasni; Serlyta, Putu Dina; Dewi, Putu Suria; Karangan, Mona Denisa; Melania, Fransiska (Jurnal Pendidikan Kewarganegaraan Undiksha, 2025)
This study aims to examine the implementation of the deep learning approach by PPKn teachers in developing honest character in grade 10 students at SMAN 4 Singaraja and to identify obstacles in the implementation process. The deep learning approach in the Independent Curriculum emphasizes in-depth, meaningful, contextual, and reflective learning, which aims not only to transfer knowledge but also to build on the approach.mindful, meaningful, And joyful which emphasizes that learning must be carried out in depth, meaningfully, and enjoyably. In the context of character education, honesty is a fundamental value that must be instilled from an early age, both in academic and social environments. This study uses a descriptive qualitative method with data collection techniques in the form of classroom observations, in-depth interviews with teachers and students, and documentation of learning activities. The data results were analyzed using the theory of Miles and Huberman, namely through data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that learning strategies such as case studies on dishonesty, reflective discussions, and social projects with the theme of honesty are effective in increasing students' understanding and practice of honest values. Civics teachers act as facilitators, motivators, and primary role models in this process. This study recommends the importance of integrating character values in active learning.